ANTIOXIDANT SYSTEM ACTIVITY IN BLOOD AS AN EARLY PREDICTOR OF POSTPARTUM ENDOMETRITIS (CLINICAL AND LABORATORY STUDY) - Kamilova Iroda Abdurasulovna; Umarov Aziz Rustamovich (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2025)
Postpartum endometritis (PE) remains one of the leading causes of maternal infectious morbidity in the postpartum period and often determines the duration of hospitalization, the need for repeat visits, and the risk of developing postpartum sepsis. Surgical delivery makes a significant contribution to the structure of postpartum infections: PE occurs after 1–3% of vaginal deliveries and up to 27% of cesarean sections, and the problem is particularly relevant against the backdrop of an increase in the frequency of cesarean sections in Uzbekistan.